Caribbean Report 18-04-1997 - Orr, Carol (anchor); Eades, David (correspondent); Brenner, Philip (interviewee); Mitchell, Keith (interviewee); Richards, Ken (correspondent); Forsyth, Justin (interviewee); Savage, Frank (interviewee) (The British Broadcasting Corporation, 1997)
The European Union has agreed to drop its dispute with the United States over an American law blocking foreign trade in Cuba. The EU will now suspend its appeal to the World Trade Organisation. In return Washington will end its block on visas for businessmen with interest in Cuba. Next, the Prime Minister of Grenada says he does not expect his visit to Cuba to create problems for Grenada/United States relations. He is scheduled to leave for Havana tomorrow on a visit he hopes will strengthen ties between St. Georges and the Fidel Castro government. Next, pro-government candidates in Haiti have been claiming that supporters of former President Jean-Bertrand Aristide are rigging results from a recent legislative elections. Officials results from the April 6th election are due on the 2nd May. Next, the international aid group Oxfam, a World Bank and IMF plan to offer debt relief to around 20% of the world’s poorest countries is in danger of failing. It is claimed that new life ought to be breathed into the initiative. Next, Tony Abbott is the next governor for Montserrat. His first priorities would be to familiarise himself with the volcanic activity there and meeting the people on the island. Next, in Britain ten black candidates have been nominated to contest the United Kingdom general elections in less than two weeks times. The number of Afro-Caribbean and other black candidates taken as a proportion of all candidates is a revealing comment on the level of apathy reported among black voters. In the final segment, are stories of Caribbean interest appearing in the British press.
1. Headlines (00:00-00:34)
2. The European Union drops its dispute against Washington over Helms-Burton for a price. Will President Clinton be able to deliver on his promise? Philip Brenner, Senior Professor at the Department of International Relations for Policy at the American University is interviewed. David Eades reports from Brussels (00:34-05:35)
3. Prime Minister, Keith Mitchell visits Cuba. Prime Minister of Grenada, Dr Keith Mitchell is interviewed (05:36-07:04)
4. The legislative elections in Haiti are being rigged by supporters of former President Jean-Bertrand Aristide (07:05-07:28)
Keywords: European Union.; Helms-Burton Act.; World Trade Organisation.; Grenada -- Foreign Relations -- United States.; Elections -- Haiti.; Oxfam.; Abbott, Tony.; Elections -- Britain.